Comparison of the Outcome of Pain Relief Between Corticosteroid Injection with Thumb Spica Cast and Casting Alone in the Treatment of de Quervain's Tenosynovitis. - Muhammad Rehman Shinwari, Muhammad Nabeel Sabir,Muhammad Sharjeel Sabir,Rana Muhammad Adnan,Muhammad Omer Kaleem (Journal of Rawalpindi Medical College, 2018)
Background: To compare the frequency of pain relief between corticosteroid injection combined with casting and casting alone in the management of de Quervain tenosynovitis. Methods: Seventy patients with de Quervain's Tenosynovitis in age ranging from 18 to 70 years were recruited for the study. Two groups each containing 35 patients were formed by dividing the patients randomly. Group A was given injection triamcinolone with thumb spica cast and group B was given thumb spica cast alone. The VAS pain score at presentation was recorded for each patient. Both groups were compared regarding pain relief by recording VAS pain score at 4 weeks after presentation. The results were analyzed with the help of SPSS version 10. A p-value of 0.05 was considered significant. Results: Mean/average age of the patients was 43.79±16.015 years (mean ± SD). In both groups, there was no statistically significant difference for the age and pre-treatment VAS pain score (p values 0.464 and 0.482 respectively). In group A (Corticosteroid injection plus thumb spica cast) there were more patients which were pain-free at the end of the study (88.5% in group A, 62.9 % in group B, p-value 0.012). Conclusion: Corticosteroid Injection plus thumb spica cast is more effective for reducing pain in de Quervain's Tenosynovitis as compared to thumb spica cast alone.